International Migration and State Sovereignty: Reconciling Human Rights Obligations with Border Control - Kudakwashe Zhou; Thomas Sheku Marah (Rechtenstudent, 2025)
The movement of people across borders has become one of the most contested issues in contemporary international law, as the sovereign prerogative of states to regulate entry, exit, and residence increasingly collides with obligations arising from international human rights and refugee law. Global migration flows driven by armed conflict, poverty, environmental degradation, and political instability have intensified this tension, placing states under pressure to manage borders while upholding the dignity and fundamental rights of migrants. This study examines the legal and political challenges that emerge when states attempt to balance border control with international human rights commitments, with particular focus on asylum seekers, refugees, and irregular migrants. It analyzes the evolving interpretation of two core international instruments the 1951 Refugee Convention and the International Covenant on Civil and Political Rights alongside relevant regional frameworks, drawing on the jurisprudence of international courts and treaty bodies. The research further explores the interaction between domestic legal systems and international treaty obligations in shaping migration governance. Key areas of legal controversy, including the principle of non-refoulement, offshore processing, and the externalization of border controls, are critically assessed. Ultimately, this study seeks to contribute to the development of legal frameworks capable of reconciling state sovereignty with the protection of migrant rights in an increasingly fragmented yet interconnected global order.